Cover Feature: Carboranyl Analogues of Celecoxib with Potent Cytostatic Activity against Human Melanoma and Colon Cancer Cell Lines (ChemMedChem 3/2019). (5th February 2019) - Buzharevski, Antonio; Paskas, Svetlana; Sárosi, Menyhárt‐Botond; Laube, Markus; Lönnecke, Peter; Neumann, Wilma; Mijatovic, Sanja; Maksimovic‐Ivanic, Danijela; Pietzsch, Jens; Hey‐Hawkins, Evamarie
Abstract : The Cover Feature shows carboranyl analogues of celecoxib, a potent COX‐2‐selective inhibitor (COXIB). Cyclooxygenase‐2 (COX‐2) has a prominent role in the occurrence and progression of various cancers. Recently, there is an expressed focus on the development of new COX‐2‐selective inhibitors (COXIBs) as potential cytostatic agents. A highly stable carborane cluster, which can serve as phenyl mimetic, was implemented in the structure of celecoxib in order to generate analogues with enhanced metabolic stability. Although the new derivatives do not act as COXIBs, they proved to have a potent cytostatic effect on various melanoma and colon cancer cell lines. Cover illustration by Menyhárt‐Botond Sárosi. More information can be found in the Full Paper by Evamarie Hey‐Hawkins et al. onpage 315 in Issue 3, 2019 (DOI:10.1002/cmdc.201800685 ).